Lentinula edodes (Shiitake) mushroom extract protects against hydrogen peroxide induced cytotoxicty in peripheral blood mononuclear cells - Kuppusamy, Umah Rani; Chong, Y.L.; Mahmood, A.A.; Indran, M.; Abdullah, N.; Vikineswary, S. (National Institute of Science Communication and Information Resources, CSIR, 2009)
Lentinula edodes (Berk) Pegler, commonly known as Shiitake mushroom has been used as medical food in Asian countries, especially in China and Japan is believed to possess strong immunomodulatory property. In the present study, the methanolic extract of the fruit bodies of L. edodes was investigated for cytoprotective effect against H(2)O(2)-induced cytotoxicity in human peripheral blood mononuclear cells (PBMCs) by measuring the activities of xanthine oxidase (XO) and glutathione peroxidase (GPx). H(2)O(2) at a concentration of 5 mu M caused 50 inhibition of PBMCs viability. the extract improved the PBMC viability and exerted a dose-dependent protection against H(2)O(2)-induced cytotoxicity. At 100 mu g/ml of extract concentration, the cell viability increased by 60 compared with tile PBMCs incubated with H(2)O(2) alone. The extract also inhibited XO activity in PBMC, while showing moderate stimulatory effect on GPx. However, in the presence of H(2)O(2) alone, both the enzyme activities were increased significantly. The GPx activity increased, possibly in response to the increased availability of H(2)O(2) in the cell. When the cells were pretreated with the extract and washed (to remove the extract) prior to the addition of H(2)O(2), the GPx and XO activities as well as the cell viability were comparable to those when incubated with the extract alone. Thus, it is suggested that one of the possible mechanisms via which L. edodes methanolic extract confers protection against H(2)O(2)-induced oxidative stress in PBMC is by inhibiting the superoxide-producing XO and increasing GPx activity which could rapidly inactivate H(2)O(2).